Coupling coordination of the water‒energy‒carbon system in three provinces of Northeastern China - Cao, Yongqiang; Li, Jing; Xie, Linfu; Yao, Jiaqi; Li, Kexin; Zhang, Ningyue; Ji, Xinhui; Wang, Mengran; Mo, Fan; Zhai, Haoran (Frontiers in Environmental Science, 2023)
Water resource consumption, energy consumption, and carbon emissions are key factors that restrict the level of regional development and affect the quality of the regional ecological environment. This study investigates three provinces in northeastern China, using remote sensing and historical data from the period 2001‒2019 to analyze the spatiotemporal trends of water and energy consumption, and carbon emissions. Using the AHP-entropy weight method, comprehensive analysis method, and system dynamics research method, the coupling relationships of the three subsystems (water‒energy‒carbon, WEC) were determined, and the development and changes over the next 20 years were simulated. The results show that: (1) Over the period 2001‒2019, the comprehensive index of the WEC system in the three northeastern provinces ranged from 0.0994 to 0.2314. (2) Over the period 2001‒2019, the coupling degree of the WEC system in the three northeastern provinces ranged from 0.9457 to 0.9985, equating to a high coupling stage level. However, the level of coupling coordination was low, with values ranging from 0.3151 to 0.4780, equating to a state of mild disorder or near disorder. (3) During the study period, water resource consumption, energy consumption, and carbon emissions all showed an increasing trend, with the former having the fastest growth rate. This study is of great significance for promoting the sustainable utilization of resources and green and low-carbon development in the three studied northeastern provinces of China.